2001
DOI: 10.1002/1521-3935(20010601)202:9<1638::aid-macp1638>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

The Aggregation Behavior of Poly(ethylene oxide)-Poly(methyl methacrylate) Diblock Copolymers in Organic Solvents

Abstract: Poly(ethylene oxide)‐poly(methyl methacrylate) and poly(ethylene oxide)‐poly(deuteromethyl methacrylate) block copolymers have been prepared by group transfer polymerization of methyl methacrylate (MMA) and deuteromethyl methacrylate (MMA‐d8), respectively, using macroinitiators containing poly(ethylene oxide) (PEO). Static and dynamic light scattering and surface tension measurements were used to study the aggregation behavior of PEO‐PMMA diblock copolymers in the solvents tetrahydrofuran (THF), acetone, chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…This is due to the difficulty of finding a selective solvent for this block copolymer that can favor the formation of micelle/inverse micelle. As reported by Edelmann et al, the solubility parameters of both PMMA and PEO are similar in most of the commercially available solvents, such as tetrahydrofuran (THF), acetone, and toluene, making the Flory−Huggins segmental interaction parameters (χ) for both polymer blocks nearly equal to each other and thus against micelle formation. This is a consequence of the strongly swollen PMMA chains of high mobility in those solvents.…”
Section: Introductionmentioning
confidence: 61%
“…This is due to the difficulty of finding a selective solvent for this block copolymer that can favor the formation of micelle/inverse micelle. As reported by Edelmann et al, the solubility parameters of both PMMA and PEO are similar in most of the commercially available solvents, such as tetrahydrofuran (THF), acetone, and toluene, making the Flory−Huggins segmental interaction parameters (χ) for both polymer blocks nearly equal to each other and thus against micelle formation. This is a consequence of the strongly swollen PMMA chains of high mobility in those solvents.…”
Section: Introductionmentioning
confidence: 61%
“…[35,36] Generally, water is the mutual solvent for both of the PEO and the PNIPAm blocks when the temperature is lower than the critical micelle temperature (CMT). The PEO-b-PNIPAm is usually considered to exist as single chains in aqueous solution, and it would form micelles with PNIPAm being the core and PEO being the corona on increasing the temperature to above the CMT.…”
Section: The Aggregation Behavior In Pure Dmf Solventmentioning
confidence: 99%
“…In their opinion, the formation of aggregation is attributed to the incompatibility between PNIPAm and PEO (v AB ), in which condition some of the PEO-b-PNIPAm chains associated together to form the structure containing PEO-rich and PNIPAm-rich domains. Adelmann et al [36] also observed the aggregation behavior of poly(ethylene oxide)-b-poly(methyl methacrylate) (PEO-b-PMMA) in mutual organic solvents (e.g., THF, DMF, acetone, chloroform, etc.). Based on the SANS and 1 H NMR experimental results, no micelle exists.…”
Section: The Aggregation Behavior In Pure Dmf Solventmentioning
confidence: 99%
“…When block copolymers are dissolved in nonselective solvents (solvents appropriate for all blocks), the copolymers are generally considered to exist as single chains. Because of the unfavorable thermodynamic interactions between different blocks, the aggregated conformation of single polymer chains was observed in some investigated systems, such as poly(ethylene oxide)‐ b ‐poly( N , N ‐dimethylacrylamide) copolymers in water and tetrahydrofuran (THF),47 poly(ethylene oxide)‐ b ‐poly(methyl methacrylate) in THF, cetone, chloroform and 2,2,2‐trifluoroethanol,48 polystyrene‐ b ‐polyisoprene copolymers in bis(2‐ethylhexyl) phthalate solution,49, 50 polystyrene‐ b ‐poly( N ‐vinylpyrrolidone) copolymers in methanol solution,51 and block copolymers of polystyrene and quaternized poly( N , N ‐diethylamino)isoprene in N , N ‐dimethylformamide, dioxane, and THF solutions 52…”
Section: Introductionmentioning
confidence: 99%